Posted by **chama** on Wednesday, March 14, 2012 at 11:02am.

Prove that sin3theta=3sintheta-4sin^3theta

## Answer This Question

## Related Questions

- maths - show that sin3theta-cos2theta =(1-sin theta)(4sin squared theta + 2sin ...
- maths - show that sin3theta-cos2theta =(1-sin theta)(4sin squared theta + 2sin ...
- aljebra - Solve the equation for cos(3theta/2).tan(3theta/2)
- math - If 3 tan theta = 4, then evaluate : 3sintheta + 2costheta / 3sintheta – ...
- trig - Solve the equation for cos(3theta/2).tan(3theta/2)for greater than or ...
- sgmic - Prove that tan theta+tan 2theta+tan 3theta=tan theta*tan 2theta*tan ...
- Maths - y = -14sin(8x)2cos(5x) - 4sin(5x)cos(8x) u = -14sin(8x) u' = -112cos(8x...
- math - cos^6A-sin^6A=cos2A(1-1÷4sin^2 2A) Prove
- math - Prove that:(3-4sin^2A) (1-3tan^2A)=(3-tan^2A)(4cos^2A-3)
- Trigonometry - Solve the equation for solutions in the interval 0<=theta<...

More Related Questions